Immunomic Investigation of Holocyclotoxins to Produce the First Protective Anti-Venom Vaccine Against the Australian Paralysis Tick, Ixodes holocyclus - Rodriguez-Valle, Manuel; McAlister, Sonia; Moolhuijzen, Paula M.; Booth, Mitchell; Agnew, Kim; Ellenberger, Claudia; Knowles, Aleta G.; Vanhoff, Kathleen; Bellgard, Matthew I.; Tabor, Ala E. (Frontiers in Immunology, 2021)
Venom producing animals are ubiquitously disseminated among vertebrates and invertebrates such as fish, snakes, scorpions, spiders, and ticks. Of the ~890 tick species worldwide, 27 have been confirmed to cause paralysis in mammalian hosts. The Australian paralysis tick (Ixodes holocyclus) is the most potent paralyzing tick species known. It is an indigenous three host tick species that secretes potent neurotoxins known as holocyclotoxins (HTs). Holocyclotoxins cause a severe and harmful toxicosis leading to a rapid flaccid paralysis which can result in death of susceptible hosts such as dogs. Antivenins are generally polyclonal antibody treatments developed in sheep, horses or camels to administer following bites from venomous creatures. Currently, the methods to prevent or treat tick paralysis relies upon chemical acaricide preventative treatments or prompt removal of all ticks attached to the host followed by the administration of a commercial tick-antiserum (TAS) respectively. However, these methods have several drawbacks such as poor efficacies, non-standardized dosages, adverse effects and are expensive to administer. Recently the I. holocyclus tick transcriptome from salivary glands and viscera reported a large family of 19 holocyclotoxins at 38-99% peptide sequence identities. A pilot trial demonstrated that correct folding of holocyclotoxins is needed to induce protection from paralysis. The immunogenicity of the holocyclotoxins were measured using commercial tick antiserum selecting HT2, HT4, HT8 and HT11 for inclusion into the novel cocktail vaccine. A further 4 HTs (HT1, HT12, HT14 and HT17) were added to the cocktail vaccine to ensure that the sequence variation among the HT protein family was encompassed in the formulation. A second trial comparing the cocktail of 8 HTs to a placebo group demonstrated complete protection from tick challenge. Here we report the first successful anti-venom vaccine protecting dogs from tick paralysis.